Risk Factors Associated With Cardiovascular Diseases Among Patients Attending Nyeri County Referral Hospital, Central Kenya - Muhu, Beatrice Wairimu (Amref International University, 2024)
Background: Globally, cardiovascular disease is among the leading causes of morbidity and premature death. Several risk factors have been shown to be associated with increased risk of acquiring cardiovascular disease. In Sub Saharan Africa, the trend has been rising steadily. Most of the population in Kenya is unaware of these risk factors. Moreover, there is lack of access to appropriate healthcare among the rural population. Few studies exist in Kenya that highlight the determinants of cardiovascular disease. Broad Objective: The aim of this study was to determine the risk factors associated with cardiovascular disease among patients attending Nyeri County Referral Hospital. Methods: This was a cross-sectional study using probability proportion to size and systematic sampling method targeting 320 respondents based in a hospital. Data was collected [from the based on?] a structured questionnaire. Analysis of the data was undertaken by using SPSS and bivariate linear regression was used to describe the relationship between the socio-demographic characteristics and the WHO CVD risk score. Study findings Hypertension, as a risk factor for cardiovascular disease, had a prevalence of 23.8% (95% CI 22.9%-24.6%), diabetes had a prevalence of 4% (95 % CI 2.92%-5.08%) while obesity had a prevalence of 13.2% (95% CI 9.5%-16.9%). Among the respondents, 21.9% took alcohol, 8.5% smoked tobacco, 34.8% engaged in moderate exercise adequately, 7.8% took fruits and vegetables daily, 38.9% took sugar, 88% of them had starchy foods more than 2 days/week and 12% took fish, poultry daily. WHO CVD risk scores showed that 79% had low CVD risk score, 16.3% and 4.4% had moderate and low CVD risk scores respectively. There was a strong association between age, gender, residence, education and employment status, income level and cardiovascular disease risk. Conclusion: Prevalence of biological risk factors was similar to national estimates. Prevalence of behavioral risk factors varied. WHO CVD risk scores demonstrated that majority had low CVD risk scores while the rest had moderate to high CVD risk scores. Several socio-demographic characteristics increased cardiovascular risk among the population.
A Research Thesis Submitted in Partial Fulfilment for the Degree of Masters in Public Health (Applied Epidemiology), Department of Community Health, School of Public Health, Amref International University
Keywords: Cardiovascular Diseases